Randomised controlled trial of the impact of haemodiafiltration on uraemic neuropathy: FINESSE study protocol. Issue 1 (15th January 2019) - Smyth, Brendan; Krishnan, Arun V; Gallagher, Martin; Kiernan, Matthew; Snelling, Paul; Hawley, Carmel; Fernando, Mangalee; Hand, Samantha; Grimley, Kim; Burman, Jenny; Heath, Anne; Kang, Amy; et al.
Abstract : Introduction: The majority of patients undergoing haemodialysis (HD) show evidence of uraemic neuropathy, a condition with no known disease-modifying treatments. The pathogenesis of uraemic neuropathy is poorly understood, but may be related to cumulative exposure to middle molecules or other solutes such as potassium. It is not known whether haemodiafiltration (HDF) reduces the progression of uraemic neuropathy. Methods and analysis: Filtration In the Neuropathy of End-Stage kidney disease Symptom Evolution (FINESSE) is a multicentre, randomised, open-label, blinded endpoint assessment, controlled trial designed to assess the impact of HDF versus HD on uraemic neuropathy. Maintenance HD patients will be randomised in a 1:1 ratio to receive HDF or HD with high-flux membranes for 4 years. The primary endpoint is the difference in the mean change in Total Neuropathy Score (TNS)—a measure of peripheral neuropathy combining symptoms, signs and nerve conduction velocity—over the study period. Secondary outcomes include change at annual timepoints in the TNS and the Neuropathy Symptom Score; and in morbidity, mortality and safety events. Ethics and dissemination: The FINESSE trial has been approved by the Ethics Review Committee of the Sydney South West Area Health Service (HREC/09/RPAH/268) and of Adventist HealthCare Limited (2012–027). When published in a peer-reviewed journal, it will be the largest and longest reported randomised trial aimed at reducing the incidence and severity of uraemic neuropathy. It will advance the understanding of the natural history of uraemic neuropathy and the influence of convective therapies on both neurophysiological and clinical outcomes. It will also allow refinement of current hypotheses surrounding the pathogenesis of uraemic neuropathy and, most importantly, may lead to improvements in the lives of the many patients affected by this debilitating condition. Trial registration number: ACTRN12609000615280.